2021
DOI: 10.3389/fphys.2021.654797
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Chronic Cough: Are Women More Likely to Cough?

Abstract: Chronic cough is a common complaint for patients to seek medical cares all over the world. Worldwide, about two thirds of chronic cough patients are females. However, in some regions of China the prevalence of chronic cough between sexes is roughly the same. Estrogen and progesterone can not only have an effect on transient receptor potential vanilloid 1 channel, eosinophils and mast cells, but also influence laryngeal dysfunction, gastroesophageal reflux disease and obstructive sleep apnea hypopnea syndrome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 78 publications
2
14
0
1
Order By: Relevance
“…For each symptom class, the total number of samples and their gender distributions are listed in Table 1. Similar to other COVID-19 related acoustic databases (Muguli et al, 2021; B. W. Schuller, Batliner, et al, 2021), the sample numbers at the two statuses are imbalanced.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…For each symptom class, the total number of samples and their gender distributions are listed in Table 1. Similar to other COVID-19 related acoustic databases (Muguli et al, 2021; B. W. Schuller, Batliner, et al, 2021), the sample numbers at the two statuses are imbalanced.…”
Section: Methodsmentioning
confidence: 87%
“…Furthermore, the age distribution is examined across all symptom conditions (see Figure 1). Apart from all three tasks, it is interesting to investigate the performance in these tasks under different genders or age ranges, as previous studies have shown gender and age differences in cough behaviour (Bai et al, 2021;Ioan et al, 2014). As shown in Figure 1, the median of the age ranges is around 30, which is used to split the data into two age groups for each task.…”
Section: Data Pre-processingmentioning
confidence: 99%
See 3 more Smart Citations